Analisis Perencanaan Pembelian Bahan Baku Dalam Kaitannya Dengan Efisiensi Bahan Baku Pada PT. Unitex - Efrianti, Desi; Marlin, Tarida; Novia, Jesica (Jurnal Ilmiah Akuntansi Kesatuan, 2015)
Purchase of raw materials is an important element in a manufacturing company because this function has a responsibility to obtain raw materials with good quantity and quality and in accordance with the requirements. Raw materials are the main source to produce and create finished goods that will be sold by company and make a profit. The production process can only be done when the supply of raw materials available in suficient quantities. The purpose ofthis study was to observe and analyze how the planning of raw materials and how they affect the efficiency ofthe availability of raw materials, as well as to deepen the blowledge of the author regarding the purchase of raw materials and raw material control. In conducting this study, the author make observations directly to the company as well as conduct interviews and analyze the data obtained. The author uses the method of descriptive analysis of qualitative data to analyze the efficiency ofplanning the purchase of raw material availability.Result of this study indicates that PT Unitex Tbk has not applied the calculation methodfor the management ofraw material inventoo. The purchase planning ofraw materials based on the needs of raw materials that can be seen from the orders of the customers. But overall, the purchase planning ofraw materials in PT Unitex is quite eficient on the availability of raw materials. It is shown that the supply of raw materials is never in a state ofzeroand is always in a state ready for production. Keywords: purchase of raw materials, purchase planning, availability of raw materials.